National park “Slobozhansky” – component of the natural and historical heritage of Ukraine - Гетьман, В. (Київський національний університет імені Тараса Шевченка, 2015)
The result of the increased anthropogenic global influence has become a planetary phenomenon of fragmentation of natural landscapes. One of the relatively preserved natural systems of landscape diversity is national park “Slobozhanskiy” in the Kharkiv region. The National Park “Slobozhanskiy” – an important center of biodiversity in Eastern Ukraine. Biotic uniqueness of its territory is largely determined by local natural and historical conditions. The article analyzes the flora and fauna of the national park, to the extent possible volume of article – retrospective prerequisites for the formation of not simple relationship in the system “man – nature” after the settlement of Sloboda Ukraine in the XVII century.

Наслідком всезростаючого глобального антропогенного впливу стало планетарне явище фрагментації природних ландшафтів. Одними із відносно збереженим природним різноманіттям є ландшафтні комплекси національного природного парку “Слобожанський” у Харківській області. Територія національного природного парку “Слобожанський” – важливий осередок біорізноманіття Східної України. Біотична своєрідність його території у значній мірі визначена місцевими природно-історичними умовами. У статті аналізується флора і фауна території національного парку, а також, у міру можливого обсягу статті, – ретроспективні передумови формування не простих відносин у системі “людина – природа” після заселення Слобідської України з XVII ст.
Національний парк “Слобожанський” – складова природно-історичної спадщини України
Alekseenko M. Rastitel’nost’ Har’kovskoj oblasti [Vegetation Kharkiv region], Har’kovskaja oblast’. Priroda i hozjajstvo, Kharkiv : Izd-vo Har’k. un-ta, 1971, pp. 80-94, [in Russian]. Bahaliy D. Istoriya Slobids’koyi Ukrayiny [History of Sloboda Ukraine], Kharkiv : Del’ta, 1993, 255 p., [in Ukrainian]. Vovk O. Vydy flory Kharkivshchyny, shcho pidlyahayut’ okhoroni [Types of Kharkiv flora to be protected], Ridnyy kray, Kharkiv : KhDPU, Vol.2, 1999, 24-34, [in Ukrinian]. Vovk O. Roslynnyy svit Kharkivs’koyi oblasti [Flora Kharkiv region], Ridnyy kray, Kharkiv : KhDPU, Vol.2, 1999, pp. 17-24, [in Ukrainian]. Het’man V.I. Ukrayins’ka model’ natsional’noho parku [Ukrainian model of the national park], Zeleni Karpaty, no. 1-2, 2011, pp. 24-27, [in Ukrainian]. Gorelova L. Redkie rastenija Har’kovshhiny [Rare plants of Kharkiv Region], Kharkiv: HNU im. V.N. Karazina, 1999, 52 p., [in Russian]. Klimov O. Pryrodno-zapovidnyy fond Kharkivs’koyi oblasti [Natural Areas Kharkiv region], Kharkiv: Rayder, 2005, 304 p. [in Ukrainian]. Epshteyn A. (eds.) Krasnokut·s’k. Zbirnyk arkhivnykh dokumentiv i materialiv [Collection of archive documents and materials], Kharkiv : Folio, 1994, 96 p. [in Ukrainian]. Materialy proektu stvorennya natsional’noho pryrodnoho parku “Slobozhans’kyy” [Materials project of national park “Slobozhanskiy”], 2009, [in Ukrainian]. Taranushenko S. Pam”yatnyky arkhitektury Slobozhanshchyny XVII- XVIII vikiv [Architecture Slobozhanshchina XVII- XVIII centuries], Pytannya istoriyi arkhitektury ta budivel’noyi tekhniky Ukrayiny, Kyiv: Derzhbudvydav URSR, 1959, pp. 44-80, [in Ukrainian]. Chyzhov M.P. Ukrayins’kyy lisostep [Ukrainian steppe], Kyiv: Radyans’ka shkola, 1961, 202 p, [in Ukrainian].
Keywords: національний природний парк; екосистема; ресурси; флора; фауна; national park; ecosystem resources; flora; fauna